Effect of multi-directional forging and ageing on fracture toughness of Al–Zn–Mg–Cu alloys. Issue 15 (12th October 2020) - Huang, Tiantian; Deng, Wenjie; Zhou, Yujie; Cao, Yanyan; Wei, Chunhua; Yan, Weilin
Abstract : Strength, ductility and fracture toughness are the most important mechanical properties of engineering materials. In this work, an Al–Zn–Mg–Cu alloy was subjected to multi-directional forging (MF) and ageing treatment. Microstructural evolution was studied by optical and electron microscopy and strength, ductility and fracture toughness were researched. After MF, the dislocation density was increased and the microstructure was refined. The strength and fracture toughness were increased, while the ductility was decreased sharply. Without compromising the strength, the ductility was improved significantly after ageing. The fracture toughness was increased further. The coarse and discontinuously distributed grain boundary precipitates were found to be responsible for higher fracture toughness of the fine-grained structure Al–Zn–Mg–Cu alloy.